Fracture mechanism analysis on the slipper retainer in axial piston pumps. (October 2017) - Xu, Liqiang; Sun, Hongfei; Xu, Shangwu
Abstract: The normal problems of a slipper retainer during operation are friction pair wear and mechanical fracture. Causes of fracture are generally investigated in terms of the strength, material, structure, and process. However, this approach does not solve these problems fundamentally. In order to determine the reason for wear and fracture, an analysis method based on the mechanism, mechanics, and microstructure is proposed to illuminate the relationship between a slipper getting stuck and slipper retainer fracture. Single and double slipper holes stuck in the slipper retainer were compared. The results showed that a piston stuck in the cylinder block is the main reason for slipper retainer fracture. Measures to avoid fracture are suggested, such as changing the piston material to one with better tribological properties.